CHARACTERIZATION OF MORBIDITY AND MORTALITY NEWLY BORN IN HOSPITALIZED NEONATAL INTENSIVE CARE UNIT - Andrea Moreira Arrué; Eliane Tatsch Neves; Andressa da Silveira; Greice Machado Pieszak (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976925947 Objective: To characterize the mortality of newborns (NB) in a Neonatal Intensive Care Unit in southern Brazil, in 2004. Method: documentary, descriptive, retrospective study. The population consisted of 302 neonates. Data collection was performed directly in the medical records, using a form own, including variables related to were conducting pre-natal care, reason for hospitalization, morbidity y causes of death. Quantitative data were descriptive statistically analyzed. Results: have to prematurity as the main reason for hospitalization and cause of death. Regarding morbidity highlights the respiratory distress syndrome of the newborn, hematological disorders and neonatal infection. Conclusions: the listed conditions during pregnancy and birth were the main cause of hospital admissions. We recommend a prenatal and postnatal quality, skilled assistance at delivery and in assisting the RN in order to reduce the rates of morbidity and mortality.